Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis guinensis Jacq.) Akibat Pemberian Berbagai Taraf Dosis Poc Rebung Bambu Di Main-Nursery - Hanif, Muhammad (CULTIVATE: Journal of Agriculture Science, 2025)
Oil palm (Elaeis guineensis Jacq.) is a strategic plantation commodity that plays an important role in Indonesia’s economic development and provides employment for millions of workers. The rapid growth of the palm oil industry has increased the demand for high-quality seedlings. Successful seedling production is largely influenced by cultivation techniques and fertilizer availability. Within the concept of sustainable agriculture, bamboo shoot liquid organic fertilizer (POC) can serve as an alternative nutrient source for oil palm seedlings. This study aimed to (1) examine the response of oil palm seedlings to various doses of bamboo shoot POC, and (2) determine the optimal dose for seedling growth. The experiment was conducted for four months (March–June 2025) at the experimental field of Politeknik Pertanian Negeri Payakumbuh, West Sumatra, using a Completely Randomized Design (CRD) with five treatments (0, 140, 280, 420, and 560 ml/polybag). Results showed significant effects on vegetative growth, with the best performance observed at 560 ml/polybag (P4).